Revistas científicas registradas no DOAJ: análise a partir do Índice H5 - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia;, 2023)
The study conducts a comprehensive analysis of the interrelations amongthe H5 Index of journals listed in the DOAJ, the per capita Gross Domestic Product(GDP) of the regions where these journals are disseminated, and the adoptedpublication language(s). To achieve this goal, the Gsm_hdata tool was employed fordata collection and analysis. It was observed that regions globally recognized forhosting journals with the highest H5 Indices coincide with those displaying thehighest per capita GDP, predominantly favoring the English language for publication.Simultaneously, regions with more modest H5 Indices house journals with a lowerpresence of English-language publications and exhibit lower averages of per capitaGDP. The presented outcomes delineate noteworthy correlations among the H5Index, per capita GDP, and the prevalence of the English language, suggesting thatthese variables play pivotal roles within the context of journal citation indices.
Scientific Journals Registered in the DOAJ: analysis based on the H5 Index
Keywords: Revistas científicas,; Acesso Aberto; Directory of Open Access Journals (DOAJ); Índice H5; Indicadores bibliométricos; Ciência da informação